211k views
0 votes
Estimate the limit.
Picture below

Estimate the limit. Picture below-example-1

2 Answers

0 votes

Answer:

what is it

Explanation:

User Pravin Bhosale
by
4.1k points
2 votes

Answer:

Hence, the limit of the expression:
\lim_(x \to 1) ((1)/(x+2)-(1)/(3))/(x-1) is:


(-1)/(9)

Explanation:

We are asked to estimate the limit of the expression:


\lim_(x \to 1) ((1)/(x+2)-(1)/(3))/(x-1)

We will simplify the expression by first taking the l.c.m of the terms in the numerator to obtain the expression as:


(3-(x+2))/(3(x+2))\\\\=(3-x-2)/(3(x+2))\\\\=(1-x)/(3(x+2))


\lim_(x \to 1) (1-x)/(3(x+2)(x-1))\\\\= \lim_(x \to 1) (-(x-1))/(3(x+2)(x-1))\\\\\\= \lim_(x \to 1) (-1)/(3(x+2))

since the same term in the numerator and denominator are cancelled out.

Now the limit of the function exist as the denominator is not equal to zero when x→1.

Hence,


\lim_(x \to 1) (-1)/(3(x+2))\\\\=(-1)/(3(1+2))\\\\=(-1)/(3* 3)\\\\=(-1)/(9)

Hence, the limit of the expression:
\lim_(x \to 1) ((1)/(x+2)-(1)/(3))/(x-1) is:


(-1)/(9)

User Jozcar
by
4.3k points